Pengaruh Kompensasi Sumber Daya Manusia, Motivasi dan Lingkungan Kerja Terhadap Kinerja Aparatur Sipil Negara - Dina Gumay Putri; Darius Antoni (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
The purpose of this study was to analyze the effect of compensation for human resources, work motivation, work environment on the work performance of the apparatus at the Department of Culture and Tourism of the Government of South Sumatra Province. In this study, the population was employees of the Department of Culture and Tourism of the Government of South Sumatra Province. In this study, the sampling technique used was a saturated sample. The number of samples is 45 people. The analysis technique used is multiple regression analysis. The results of the first hypothesis (H1) indicate that HR compensation has a positive and significant effect on employee performance. Employees have received HR compensation in accordance with the results of their performance so that employees will work responsibly and in accordance with established operational standards. The results of the second hypothesis (H2) indicate that work motivation has a positive and significant effect on employee performance. Employees' work motivation will improve employee performance to achieve company goals. The results of the third hypothesis (H3) indicate that the work environment has a positive and significant effect on employee performance. A working environment condition is said to be good if employees can carry out activities optimally, healthy, safe, and comfortable. Therefore, the determination and creation of a good work environment will greatly determine the success of achieving organizational goals. Simultaneous testing of HR compensation (X1), Work Motivation (X2), Work Environment (X3) on Employee Performance (Y) Ha is accepted, meaning that it shows that there is a positive and significant influence on HR Compensation, Motivation and Work Environment together ( Simultaneous) on the Performance variable at the Culture and Tourism Office of South Sumatra Province.